Effect of Chitosan Addition on Porosity of Rice Husk Calcium Silicate Used for Free Fatty Acid Adsorbent from Palm Oil - Saur Lumban Raja; Olwin Butarbutar (Journal of Chemical Natural Resources, 2024)
Studies have been done on developing calcium silicate pores derived from rice husk with and without including chitosan as a template. The chitosan solution was supplemented with sodium silicate derived from rice husk, and then CaCl2 was added. The calcium silicate was calcinated at 900ÂºC for 4 h. The calcium silicate obtained was characterized using X-ray diffraction (XRD), fourier transform infrared (FT-IR), and Brunauer-Emmett-Teller (BET)  analysis. The XRD analysis showed the presence of diffraction peaks corresponding to Wollastonite (CaSiO3) crystals, Wollastonite 2m (CaSiO3), Alite (Ca3SiO5), and larnite (Ca2SiO4). Next, the FT-IR spectrum exhibits Si-O-Si, Si-O-Ca, and Si-OH functional groups, suggesting the presence of calcium silicate material. The BET study of calcium silicate using chitosan templates revealed a pore size of 3.88 nm, a pore volume of 0.1577 cc/g, and a surface area of 81.1519 m2/g. The BET analysis results obtained differed from those of the BET analysis of calcium silicate conducted without using chitosan templates, which were 2.06 nm, 0.069 cc/g, and 13.531 m2/g, respectively. The developed mesoporous calcium silicate was employed as an adsorbent to decrease the concentrations of free fatty acids in palm oil. The acid-base titration method is used to evaluate quantities of free fatty acids. The results obtained from the computation of free fatty acid levels indicate a decline in the concentration of free fatty acids in palm oil. The concentration of free fatty acids derived from palm oil was 1.23%. Therefore, mesoporous calcium silicate-free fatty acids at a concentration of 1.06% resulted in an 86.1% reduction.